Lenalidomide-based combined therapy induced alterations in serum proteins of multiple myeloma patient: a follow-up case report and overview of the literature - Senthilkumar, C.S.; Ganesh, N. (Experimental Oncology, 2012)
Aim : Multiple myeloma (MM) is a malignant neoplasm of plasma cells (PC) derived from the bone marrow (BM) origin. The present case report was aimed to monitor the efficiency of lenalidomide-based combined therapy (LBCT) induced alterations in serum proteins of 42-year-old female MM patient. Besides, in the context of case report we also present an overview of the literature describing LBCT. Study design: Serum protein electrophoresis (SPEP) was performed in three visits (V1-V3) to monitor the disease status of the patient and her treatment response to LBCT. Level of monoclonal protein (M-protein) was measured through cellulose acetate zone electrophoresis and quantified by densitometer in follow-up investigations after therapy intervals. Results: A significant reduction of M-protein in γ-globulin region was observed (P < 0.007) after receiving LBCT. However, the condition depicted hyper γ-globulinemia. β-globulin (P < 0.002) and α2-globulin(P < 0.047) was suppressed from the initial visit and subsequent follow-up also indicated the status of hypoglobulinaemia. Although, serum albumin level was found to be increased after therapy (P < 0.016), hypoalbuminaemia was also noticed before and after LBCT. Conclusion: On the basis of this case report and pertinent literature, we conclude that LBCT is more efficient in the treatment of MM and has significant role in serum protein alterations especially in the reduction of M-protein in the MM patients.